Diagnosis of the quality of service, in customer service, at the National University of Chimborazo- Ecuador - Salazar Yépez, Wilfrido (2016)
The purpose of this article is to determine the quality of service of improvements in the enrollment processes at the National University of Chimborazo- Ecuador. This cross-sectional research is the result of a field work, where an analysis of the collected information was carried out, through surveys applied to the students, through the SERVQUAL model, afterwards, comparing these found aspects and determining The gap between perceptions and expectations, thus determining the quality of service. The results show that the quality of service is regular according to the attitude of the customers.